NOTE ON THE CATCHES OBTAINED IN HOOKS-AND-LINES BY MECHANISED VESSELS AT SASSOON DOCKS, BOMBAY, DURING 1971 - Pillai, S Krishna (Indian Journal of Fisheries, 2011)
The species composition of the catches obtained in hooks-and-lines by mechanfsed vessgls at Sass(>6n docks, Bombay, 1971, is) p-raented. The eels (51.3%) and catfish (39.9%) were the major components of the total catch, followed by Carcharius spp. (4.6%), Rays (2.0%), Pomadasys hasia (1.9%). The rest of the fishes were caught in small quantities, forming less t h a n l% of the total landings